Difusión de contenidos culturales en los medios de comunicación y su impacto en las Comunidades Indígenas y Pueblos Montubios del Ecuador - Cevallos Peña, Luis Angel (2021)
In the following research, it was intended to carry out the analysis of the dissemination of cultural content in the media and from that also the impact of the indigenous communities and Montubio peoples of Ecuador, where a qualitative research will be used in which it will be based on different thoughts of article authors, magazines, among others. When we focus on investigating this topic, we must take into account the culture since it has a variety of meanings and particular characteristics that have been the object of multiple analyzes of studies around the world. To support this research project, it was decided to develop it under the qualitative modality. That is, exploratory type, where by means of this investigative method, it will seek to analyze all the arguments that are presented in the investigation, in order to generate an objective vision of each of the theoretical and technical aspects of the different topics, subtopics of the investigation, always directed with the objective of the project which is: Determine the dissemination of cultural content in the media on the impact of indigenous communities on the Montubio peoples of Ecuador. Once the case study is completed, the conclusions are presented at the end of the investigation in a sequential order. It was determined that the dissemination of cultural content is very useful for people's learning.